Evolution of Maritime Security in the Gulf of Guinea - Shaojie, Liu (Kashere Journal of Politics and International Relations, 2024)
Maritime Security in West Africa and the Gulf of Guinea is an emerging issue that will dominate global conversations in the years to come. Despite the immense importance this region holds both historically and in contemporary times in global trade and economy, little scholarly attention have been paid to the maritime environment of the Gulf of Guinea, which therefore has led to a neglect of most of the maritime crimes and insecurity in this region, leading to a loss of revenue and economic stability in the region. This study will therefore focus on a historical analysis of the maritime environment of West Africa from the earliest times to the contemporary times, with more attention paid to the huge economic prospect this region holds, as well as the challenges to maritime security in the region. This study consulted predominantly secondary sources from Journals, website articles and various reports from the United Nations official publication and Maritime Agencies to arrive at its findings. This study will therefore examine in- depth the maritime environment of the Gulf of Guinea with emphasis on the importance this region holds in the global economy